Optimization of polysaccharides extraction from quince peels: partial characterization, antioxidant and antiproliferative properties - Dammak, Mariem Itaimi; Mzoughi, Zeineb; Chakroun, Ibtissem; Mansour, Hedi Ben; Le Cerf, Didier; Majdoub, Hatem (Natural product research, 2020)
In this study, Box-Behnken Design was used to optimize the ultrasonic extraction of polysaccharides from quince peels (QPPs) by ascorbic acid and the effect of extraction temperature, extraction time and pH was evaluated. Under optimized conditions of temperature 90 °C, 60 min sonication time and pH = 3.26, the extraction yield, the galacturonic acid yield and the concentration of sample required to scavenge 50% of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic) acid (ABTS) values of QPPs were respectively 10.25%, 3.86% and 1.35 mg/mL. The QPPs extracted under optimum conditions was characterized by Fourier transform infrared spectroscopy (FTIR), Nuclear magnetic resonance ( 1 H NMR) and Size exclusion chromatography (SEC/MALS/VD/DRI). The monosaccharide analysis revealed that arabinose was the most abundant, followed by galactose, glucose, mannose and xylose. Moreover, QPPs showed significant antioxidant activities (2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric- reducing antioxidant power (FRAP)) and reduced viability of human Caco-2 and murine B-16 cell lines in a dose-dependent manner. Hence QPPs could be used as antitumor agent in functional foods andpharmaceutical industries.